The evaluation system for the fishing harbor transition to sustainable sailing-yacht tourism - Hsu, Cheng-Yu; Shen, Ye; Mikulić, Josip (Frontiers in Sustainable Tourism, 2025)
IntroductionFishing harbor cities often face decline due to the depletion of fishing resources. In response, this study aims to develop an expert evaluation system to assist in transitioning these harbors toward sustainable sailing-yacht tourism. Such a transition aligns with the objectives of Sustainable Development Goals (SDGs) 14 (Life Below Water) and 11 (Sustainable Cities and Communities).MethodsTo construct the evaluation framework, the Analytical Network Process (ANP) was used to determine the interdependent relationships among criteria, while the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied to rank and prioritize alternatives. This integrated approach facilitated a comprehensive evaluation model for sustainability transitions in harbor redevelopment.ResultsAn empirical case study conducted in the Asia-Pacific region demonstrated the application of the expert system in selecting an ideal fishing harbor for redevelopment. The combined ANP-TOPSIS model effectively identified the most suitable harbor by systematically analyzing multiple dimensions related to sustainable tourism development.DiscussionThis research contributes to the planning and development of sustainable harbors, urban areas, and sailing-yacht tourism. It offers a comprehensive evaluation model grounded in expert decision-making methods. Furthermore, the findings suggest that fishing harbors, especially those in archipelagic regions, possess significant potential for transformation into sustainable sailing-yacht tourism destinations, supporting broader SDG implementation efforts.